Pituitary macrophages in homeostasis, development and disease - Lehtonen, Henna (My University, 2022)
Tissue-resident macrophages are the major contributors to tissue homeostasis, development and function. Macrophages populate tissues already during embryonic development forming unique pools in tissues. These distinct pools are involved in the development and function of the endocrine system. The pituitary gland is a major endocrine gland regulating the hormone secretion from peripheral target tissues maintaining the body’s overall homeostasis. The composition of macrophages or their contribution to the function or development of the pituitary gland is not known. Despite of the crucial roles of macrophages in tissue homeostasis and function, macrophages involve in tumorigenesis. The tumor microenvironment induces changes in macrophage phenotypes converting them to harmful phenotypes, tumor associated macrophages. Tumor associated macrophages contribute to angiogenesis, invasiveness of cancer cells and tumor growth. The functionality of pituitary macrophages in adenomas is not known. In this thesis, the aim was to resolve the origin of pituitary macrophages and furthermore to study spatial relationships of macrophages and endocrine cells in the pituitary gland, and shed light on their function in a steady and diseased state in mice. The hypothesis was that the pituitary gland houses macrophages from all three origins, from the yolk sac, fetal liver and bone marrow, in steady state. To resolve the embryonic origins, cell-fate mapping studies were conducted, following the fate of labelled yolk sac-derived macrophages. The macrophage compartments during the postnatal development of mice were studied further. Spatial relationships between the pituitary macrophages and endocrine cell types were studied with, two different staining methods to visualise the gland in 3D with a confocal microscope. The functionality of the pituitary resident macrophages was studied in retinoblastoma deficient mice that develop pituitary adenomas in adult mice. In this thesis, the origin of pituitary macrophages was resolved. In the mice’s prenatal and postnatal pituitary gland, macrophages have originated from the yolk sac and fetal liver. The yolk sac-derived macrophages dominated the immunolandscape in the mouse pituitary gland. During the postnatal development, two distinct macrophage populations were identified. Firstly, embryonic-derived macrophage population was formed when fetal liver-derived macrophages shifted their phenotype. Secondly, bone marrow-derived monocytes infiltrated into the pituitary gland and differentiated into tissue-resident macrophages. However, despite the monocyte infiltration, the embryonic derived macrophage population was the major one in the pituitary gland through the mice development. The spatial relationships of macrophages and endocrine cells remains unsolved. The study of functionality of macrophages in disease suggested that retinoblastoma deficient mice do not develop adenomas at 6 months of age and the study will continue in the future with 9-10 months old mice.

Kudosspesifiset makrofagit osallistuvat kudoksien kehitykseen, elimistön sisäisen tasapainon ylläpitoon ja kudosten toimintaan. Kudosspesifiset makrofagit siirtyvät kudoksiin jo alkionkehityksen aikana ja muodostavat kudoksiin ainutlaatuisia solupopulaatioita, jotka voivat säilyä ja proliferoitua aikuisuuteen asti. Nämä makrofagipopulaatiot osallistuvat umpieritysjärjestelmän kehitykseen ja toimintaan. Aivolisäkkeellä on merkittävä rooli umpieritysjärjestelmässä, jossa se säätelee hormonien eritystä perifeerisistä umpirauhasista ylläpitäen elimistön tasapainoa. Kudospesifisten makrofagien kokoonpanoa tai populaation osallisuutta aivolisäkkeen toimintaan ja kehitykseen ei ole tutkittu. Vastoin makrofagien kudosten tasapainotilaa ylläpitäviä toimintoja, makrofagit osallistuvat kasvainten muodostumiseen. Syöpäsolujen luoma mikroympäristö kudoksessa indusoi muutoksen makrofagien fenotyypeissä, saaden aikaan haitallisia makrofageja. Haitalliset makrofagit edistävät angiogeneesiä, syöpäsolujen invasiivisuutta ja kasvaimen kasvua. Aivolisäkkeen makrofagien osallisuutta aivolisäkekasvaimissa ei vielä tiedetä. Tämän tutkielman tavoite oli selvittää hiiren aivolisäkkeen makrofagien alkuperä. Lisäksi tavoitteena oli tutkia aivolisäkkeen makrofagien ja endokriinisolujen spatiaalisia suhteita sekä makrofagien toiminnallisuutta homeostaasissa ja sairaudessa hiirissä. Hypoteesina oli, että aivolisäkkeen makrofagit ovat peräisin kolmesta lähteestä, ruskuaispussista, alkion maksasta ja luuytimestä. Tutkimuksessa selvitettiin leimattujen makrofagien kulkeutumista ruskuaispussista hiiren aivolisäkkeeseen ja miten kudosspesifiset makrofagi populaatiot muuttuvat hiiren yksilönkehityksen aikana. Makrofagien ja endokriinisolujen välisiä suhteita havainnollistettiin kahdella eri immunohistokemiallisella värjäysmenetelmällä ja konfonkaalikuvantamisella. Makrofagien toiminnallisuutta tutkittiin hiirimallilla, jossa hiirille kehittyy aivolisäkkeen etulohkoon kasvain. Tässä tutkielmassa todistettiin, että makrofagit ovat läsnä aivolisäkkeessä ennen hiiren syntymää ja hiiren yksilönkehityksen ajan. Alkiossa ja vastasyntyneen hiiren aivolisäkkeessä makrofagien osoitettiin olevan peräisin sekä ruskuaispussista että alkion maksasta. Suurin osa hiiren aivolisäkkeen makrofageista oli peräisin ensimmäisestä populaatiosta eli alkion ruskuaispussista. Hiiren syntymän jälkeen havaittiin aivolisäkkeessä kaksi eri makrofagipopulaatiota. Ensiksi, alkion maksasta aivolisäkkeeseen kulkeutuneiden makrofagien fenotyyppi muuttui ja aivolisäkkeeseen muodostui yksi populaatio, joka sisälsi sekä ruskuaispussista että alkion maksasta tulleet makrofagit. Toiseksi, luuytimen tuottamat monosyytit kulkeutuivat aivolisäkkeeseen ja erilaistuivat kudosspesifisiksi makrofageiksi, muodostaen toisen populaation. Hiiren aivolisäkkeen makrofagien ja endokriinisolujen välisiin spatiaalisiin suhteisiin tutkimus ei tuonut lisäinformaatiota. Makrofagien funktionaalisuuden tutkiminen kasvaimen kehityksen aikana viittasi, että tutkimuksessa käytettyihin hiiriin ei kehittynyt kasvainta kuuden kuukauden iässä. Jatkotutkimukset tullaan tekemään vanhemmilla, noin 9—10 kuukauden ikäisillä hiirillä.
Keywords: Tissue-resident macrophage, cell-fate mapping, pituitary gland, endocrine cell, flow cytometry, immunohistochemical staining